Body Dissatisfaction in Overweight Adolescents: The Role of Self Compassion and Gender - Meitasya, Brigitta Komala; Sugiariyanti, Sugiariyanti (Universitas Negeri Semarang, 2023)
The body changes during adolescence, from puberty to adulthood. Late adolescents generally have completed physical development and grown to their full adult height. These changes make them pay great attention to their body. Females tend to regard a slender body shape as attractive, while males tend to perceive a more masculine muscular body shape as attractive. They might feel that their body is not as good as other people, especially adolescents who are overweight. Body dissatisfaction refers to holding negative thoughts or feelings about one’s body image. Those who are dissatisfied with their body will describe the difference between their subjective perception of their body and their ideal body image. Individuals’ attitude who are patient, kind, and understanding instead of judging themselves when facing shortcomings is known as self-compassion. The first purpose of this research was to find out the relationship between self-compassion with body dissatisfaction among overweight adolescents, and the second was how body dissatisfaction differs between males and females. The sample in this research used purposive sampling and obtained 103 late adolescent participants who had BMI > 23kg/m². Measuring tools used in this study were the Indonesian version of Self-Compassion Scale and the Body Shape Questionnaire-34. Based on the correlation test results obtained a negative relationship between self-compassion with body dissatisfaction. So if overweight adolescents’ self-compassion is getting higher, their body dissatisfaction becomes lower and vice versa. The difference test showed that females were more dissatisfied with their bodies than males. In general, the level of both self-compassion and the level of body dissatisfaction of participants were at medium category.